Auditoria financiera al área de inventario de mercancías de la Asociación Club Campestre de Armenia con corte a diciembre 31 de 2010 (2012)
The inventories constitute one of the most susceptible components to manipulations, for this reason the Armenia´s Club Campestre Association should to implement controls that permit to manage its resources accordingly, focus specifically to the adjustments (lacking and remainders) originated at the different sale outlets, storage and restaurants monthly. Audit realized into this company, is only descriptive and the analysis made was addressed from the experiences and observations realized at the audited area. For its development began whit the planning stage, whereby collected general information to the company, in order to know its activity, organizational structure and the functions performed by the staff; subsequently proceeded with the implementation phase, where applied programs and questionnaires which allowed to detect the risks in the studied area.